Applications and numerical simulations of Heat Pipe technologies in space thermal control system. (26th November 2008) - Du, Wenjing; Cheng, Lin; Luan, Tao; Xin, Gongming
A space detector is sampled to introduce applications and thermal control performances of conventional and novel Heat Pipes (HPs). The internal two-phase change process brings HPs excellent heat transfer properties and complicated numerical calculations. Based on space design experience and experimental researches, numerical simulations of HPs can be simplified when they are serving as space thermal control hardware. Simplification is accepted in this paper and explored through a practical thermal control system design. Related thermal vacuum tests are performed to verify simplified model. Results show such assumption can bring acceptable results and less computation time to a real application.